Application of quantum mechanics/molecular mechanics methods in the study of enzymatic reaction mechanisms. (1st September 2016) - Sousa, Sérgio Filipe; Ribeiro, António J. M.; Neves, Rui P. P.; Brás, Natércia F.; Cerqueira, Nuno M. F. S. A.; Fernandes, Pedro A.; Ramos, Maria João
Abstract : Quantum mechanics/molecular mechanics (QM/MM) methods offer a very appealing option for the computational study of enzymatic reaction mechanisms, by separating the problem into two parts that can be treated with different computational methods. Hence, in a QM/MM formalism, the part of the system in which catalysis actually occurs and that involves the active site, substrates and directly participating amino acid residues is treated at an adequate quantum mechanical level to describe the chemistry taking place. For the remaining of the enzyme, which does not participate directly in the reaction, but that typically involves a much larger number of atoms, molecular mechanics is employed, traditionally through the application of a biomolecular force field. When applied with care, QM/MM methods can be used with great advantage in comparing, at a structural and energetic level, different mechanistic proposals, discarding mechanistic alternatives and proposing new mechanistic pathways that are consistent with the available experimental data. With time, diverse flavors within the QM/MM methods have emerged, differing in a variety of technical and conceptual aspects. Hence present alternatives differ between additive and subtractive QM/MM schemes, the type of boundary schemes, and the way in which the electrostatic interactions between the two regions are accounted for. Also, single‐conformation QM/MM, multi‐PES approaches, and QM/MM Molecular Dynamics coexist today, each type with its own advantages and limitations. This review focuses on the application of QM/MM methods in the study of enzymatic reaction mechanisms, briefly presenting also the most important technical aspects involved in these calculations. Particular attention is dedicated to the application of the single‐conformation QM/MM, multi‐PES QM/MM studies, and QM/MM‐FEP methods and to the advantages and disadvantages of the different types of QM/MM. Recent breakthroughs are also introduced. A selection of hand‐picked examples is used to illustrate such features. WIREs Comput Mol Sci 2017, 7:e1281. doi: 10.1002/wcms.1281 This article is categorized under: Structure and Mechanism > Computational Biochemistry and Biophysics Structure and Mechanism > Reaction Mechanisms and Catalysis Electronic Structure Theory > Combined QM/MM Methods Abstract :